Silaturahmi Sebagai Upaya Moderasi Beragama di Indonesia (Studi Analisis Surah An-Nisa' (4) Ayat 1 dan Surah Maryam (19) Ayat 96) - Nurhayati, Nurhayati (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2024)
In recent years, cases of religious blasphemy have frequently occurred in Indonesia. According to the Indonesian Legal Aid Foundation (YLBHI), there were 38 cases of blasphemy between January and May 2020 in several provinces, such as South Sulawesi, East Java, North Maluku, and West Java, which targeted children aged 14 years, 15 years, and 16 years through social media. The irony is that this case attacks the age of children and adolescents, who should be the hopeful generation of Indonesia in the future to be more advanced, including in maintaining the integrity and harmony of religious communities in Indonesia. But in fact, they commit acts of blasphemy, which can lead to polemics or disputes. The method used in this article is qualitative with the type of library research. This article will describe three problem formulations: 1) How is religious moderation in Indonesia? 2) What is the meaning of friendship and psychological struggle? 3) How is silaturrahmi an effort to moderate religion in Indonesia? In the Qur'an'n surah an-NisÄ' (4) verse 1 and sura Maryam (19) verse 96, Allah commands to maintain brotherhood (friendship), both amongh fellow Muslims and non-Muslims. Because this can facilitate communication and a sense of brotherhood, mutual respect arises for both fellow Muslims and non-Muslims, and religious moderation in Indonesia can be realized.